As fronteiras do trabalho digital: autonomia, flexibilidade, criatividade e sincronia temporal - Pelegrini, João Gabriel Selles (2023)
Starting from the theme of autonomy/subordination of labour in the context of capitalist domination, this paper analyses the work process of digital workers linked to the software development process. As a central problem, we question the supposed autonomy, flexibility and creativity that would define this type of work, especially when compared to types that would be subordinated to management schemes such as Taylor-Fordism. In order to investigate this problem, we analysed the work process of 16 digital workers through semi-structured interviews. This study is based on the following analytical hypothesis: the market demand for certain skills, such as responsibility and autonomy, operation and creativity, organisation and flexibility, results in flexible working hours when they express the logic of a synchronous temporal organisation of the work process. This synchrony is expressed in the possibility of the work process taking place at the same time as activities that would otherwise be free time. Synchrony is also found in the combination of quantitative metrics (hours, days, weeks, sprints, measures set by companies and measured by platforms) and qualitative metrics (deliveries and what is delivered, problem solving, productivity of time in relation to the amount spent, for example). From the research we have found that the skills mentioned above are ways of working and living that are shaped by this temporal logic and that they produce a digital worker who is always connected to the demands of the company and always ready to start their work process, insofar as they are responsible for the market objectives of those who employ them, flexible in relation to the demands and forms of management needed to organise digital work processes, and finally capable of performing the activities needed to fulfil what is required of them as useful in their workforce. However, digital workers show that, to the extent that they incorporate this way of living and working, they either adapt to it, reproducing the organisational principles of the work process and the underlying temporal logic, or they oppose and resist this temporal regime, developing thoughts that are critical of it.